ANTIOXIDATIVE CHARACTERISTICS OF BEVERAGES MADE FROM A MIXTURE OF LEMONGRASS EXTRACT AND GREEN TEA [Studi Karakteristik Antioksidan Minuman Campuran Ekstrak Serai dan Teh Hijau] - Jeremia Manuel Halim; W. Donald R. Pokatong; Jessica Ignacia (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Combination of lemongrass extract and green tea infusion is expected to produce functional beverage that has potential antioxidant activity as compared to individual materials. This research was aimed to investigate the appropriate solvent type and extraction methods to produce lemongrass extract with highest antioxidant activity and also to investigate the antioxidant characteristic of beverages prepared from a mixture of lemongrass extract and green tea. Lemongrass were subjected to extraction under reflux and maceration using three type of solvents (distilled water, ethanol, and ethyl acetate). The resulting extracts were assessed for their total phenolic content, total flavonoid content, and antioxidant activity. Extraction under reflux and using ethanol as solvent resulted in extract with best antioxidant activity (IC50=158.70±47.88 mg/L for reflux method and 103.73±8.03 mg/L for ethanol). This extract was combined with green tea with several ratios (lemongrass extract to green tea [w/w] = 1:3; 1:2; 1:1; 2:1; 3:1). Four level of stevia were used in the beverages (0, 200, 400, 600 ppm). Beverages made with lomogass: tea ratio of 1:3 and 1:1 (w/w) and 600 ppm stevia turned out to be beverages with the highest antioxidant activity (IC50=271.83±44.48 mg/L and 287.15±36.25 mg/L for ratio 1:3 and 1:1 [w/w] consecutively, 301.59±80.89 mg/L for stevia level 600 ppm). Hedonic testing on beverages revealed that beverage made from lemongrass: tea ratio 1:1 [w/w] ratio with addition of stevia at 600 ppm is the most preferred based on color, aroma, and overall acceptance.